Phenolics diversity among wild populations of Salvia multicaulis: as a precious source for antimicrobial and antioxidant applications. Issue 5 (4th March 2022) - Tavan, Mansoureh; Azizi, Ali; Sarikhani, Hassan; Mirjalili, Mohammad Hossein; Rigano, Maria Manuela
Abstract: The genus Salvia L. belongs to the Lamiaceae family including several known species rich in natural compounds that are extensively used in pharmaceutical, food, and cosmetic industries. Salvia multicaulis populations contain a broad diversity of flavonoids and phenolic acids. The present study aimed to explore biological and pharmacological effects including antimicrobial and antioxidant activities of nineteen S. multicaulis populations ( SMPs ) grown in Iran for the first time. High content of rosmarinic acid (RA) in SMP12 (Gazan) (5.65 ± 0.33 mg/g DW) caused high antimicrobial activity against two bacteria ( Staphylococcus aureus, Escherichia coli ) and the fungus Candida albicans, while methanolic extract of SMP1 (Taleghan) showed high antioxidant activity due to high content of salvianolic acid A (SAA) and quercetin (0.53 ± 0.04 and 0.49 ± 0.12 mg/g DW, respectively). Altogether these results can be considered for further commercial exploitations to meet the demands of the food and pharmaceutical industries.